Moving forward : the future of consumer credit and mortgage finance - Retsinas, Nicolas Paul, 1946-; Belsky, Eric S. (James A. Johnson metro series., 2011)
"Explores what caused the housing and mortgage crisis and provides remedies to repair the damage to ensure fairness, protect consumers, and guarantee soundness of the financial system without stifling innovation and overly restricting access to credit and consumer choice"--Provided by publisher